Coralliodrilus leviatriatus gen. et sp.n., a marine tubificid (Oligochaeta) from Bermuda - Erséus, C. (Sarsia, 1979)
A new tubificid genus, Coralliodrilus, is established for C. leviatriatus sp.n. from coral reef sands in Bermuda (NW Atlantic). The species is related to Phallodrilus Pierantoni, but it is distinguished from previously known Phallodrilinae in that its atria do not bear external prostate glands.